Solution of Radiative Casson Hybrid Nanofluid Flow in a Permeable Rotating Cone with Nanolayer and Mixed Convection - AROLOYE , Soluade Joseph; AKINPELUMI, Bolaji David (ABUAD Journal of Engineering and Applied Sciences, 2024)
The research investigates the MHD Casson hybrid nanofluid in the presence of thermal radiation, nanolayers, and mixed convection inside a porous, permeable rotating cone. A slip boundary condition was applied for the problem. The governing flow model describing the problem captures Darcy-Forchheimer, mixed convection, thermal radiation, and dissipation. The coupled PDEs representing flow are obtained and transformed to ODEs via similar variables. The obtained ODEs are solved numerically by the shooting method together with the order six Runge Kutta method. MAPLE mathematical software is used to code and simulate the problem. The effects of embedded flow parameters (tangential and azimuthal velocities, thermal field, Nusselt number, and skin friction coefficient) are presented graphically and in tabular form and discussed in details. The results reveal that higher interfacial nanolayer parameters increase the thermal field. The magnitude of heat transfer rate boosts via greater fluid material and thermal radiation values, while it diminishes through the Prandtl number and Eckert number.